THE POTENSIAL OF JUNGGUL (Crassocephalum crepidioides) AND SPINACH (Amaranthus tricolor L.) AS HYPERACCUMULATORS OF LEAD (Pb) ON THEIR GROWTH AND ACCUMULATION - nurwahdania nurwahdania; Mahayu Woro Lestari; Anis Rosyidah (AGRONISMA, 2022)
Lead metal in agriculture is one of the pollutants that accumulates a lot in the land due to residues of chemical fertilizers and pesticides. Phytoremediation is an effort to clean up contaminating materials in the soil and water using certain plants that have the ability to absorb heavy metals more than normal. This study was conducted to compare the ability of junggul and spinach plants to absorb heavy metals due to the application of various doses of lead Pb. This research is a polybag experiment using a simple randomized block design (RAK), namely: treatment T1, T2, T3 (Junggul Plants 0; 3; 6 g/polybag). Treatment T4, T5, T6 (Spinach 0; 3; 6 gr/polybag). Variables observed included plant height, number of leaves, leaf area, chlorophyll content, fresh weight of shoots and roots, dry weight of shoots and roots and concentration of Pb in the shoots and roots. The results showed that the growth of spinach plants increased compared to junggul plants. Increasing the dose gave an insignificant increase in growth. However, higher doses caused a significant reduction in growth. The fresh weight of roots and shoots of spinach plants increased significantly on average by 16.40 g and 33.41 g compared to junggul plants by an average of 10.10 g and 22.35 g, respectively. Junggul and spinach plants accumulated more Pb in the roots with an average lead concentration of 0.96 and 3,38. These results suggest spinach plants as hyperaccumulator plants compared to junggul plants because they absorb more heavy metals.